A paradigm shift in education: pedagogy, standpoint and ethics of care. Issue 3 (1st September 2016) - MacGill, Bindi
Abstract: This paper explores how ethics of care informs pedagogical practices in schools. Ethics of care is located within social constructivism that centralises a student centred approach to learning. In so doing, teachers engage students in learning within a relationship of reciprocity. This paper examines the ways in which social reproduction is maintained through normative ethics of care practices that is positioned as culturally neutral in schools. This paper argues for a critical examination of how the teaching/learning nexus is informed by and constrained within the paradigm of white ethics of care in education. There is a particular focus on Indigenous students' "positionality" in the Australian context throughout the paper and it argues for de-colonising strategies in teaching and schooling. These strategies include, negotiating difference within an ethics of care of reciprocity and recognition through the use of standpoint theory as both method and methodology.